2014
DOI: 10.1101/lm.033332.113
|View full text |Cite
|
Sign up to set email alerts
|

AMPK agonist AICAR improves cognition and motor coordination in young and aged mice

Abstract: Normal aging can result in a decline of memory and muscle function. Exercise may prevent or delay these changes. However, aging-associated frailty can preclude physical activity. In young sedentary animals, pharmacological activation of AMP-activated protein kinase (AMPK), a transcriptional regulator important for muscle physiology, enhanced spatial memory function, and endurance. In the present study we investigated effects of AMPK agonist 5-aminoimidazole-4-carboxamide riboside (AICAR) on memory and motor fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 67 publications
6
83
0
Order By: Relevance
“…Some studies showed that systemic administration of the AMPK agonist AICAR increased spatial memory and improved motor function in young and old female mice (Kobilo et al, 2014;Kobilo et al, 2011). Other studies found that the activation of AMPK impaired long-term spatial memory (Dash et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed that systemic administration of the AMPK agonist AICAR increased spatial memory and improved motor function in young and old female mice (Kobilo et al, 2014;Kobilo et al, 2011). Other studies found that the activation of AMPK impaired long-term spatial memory (Dash et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that AMPK has a crucial role in cognitive decline and memory dysfunction, which are the most characteristic symptoms of Alzheimer's disease (DiTacchio et al, 2015;Du et al, 2015). Although inconsistent findings have been reported regarding the role of AMPK in the formation of spatial memory (Dash et al, 2006;Kobilo et al, 2014;Kobilo et al, 2011), these findings indicate that AMPK activity is involved in learning and memory processes. However, little is known about the role of AMPK activity in the hippocampus in contextual fear memory formation.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms by which acute AMPK activation increases ischemic damage remains unclear, but increased glucose uptake due to unregulated glucose transporters in the reperfusion phase, enhanced lactate accumulation, and increased autophagy likely contribute to increased neuronal death after ischemic reperfusion (McCullough et al 2005;Li et al 2007;Arsikin et al 2012). A recent study has shown that GSK-3b acts as a critical sensor for anabolic signaling and regulates AMPK; others have found that AMPK activation mediates learning and memory (Suzuki et al 2013;Kobilo et al 2014). To address the role of AMPK in the neuroprotective and cognitive benefit of GSK-3b inhibition, we treated AMPK-a2 deficient mice with GSK-3b inhibitor VIII.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced circulating catecholamines ultimately lead to insulin resistance [8] . The ability to control the blood glucose level progressively reduces during the life span [17,18] . A gradual decline in skeletal muscle glucose uptake was observed during the phase of growth [18,19] .…”
Section: Introductionmentioning
confidence: 99%
“…The ability to control the blood glucose level progressively reduces during the life span [17,18] . A gradual decline in skeletal muscle glucose uptake was observed during the phase of growth [18,19] . Variations of glucose transporters (GLUTs) in the skeletal muscle have been reported, namely, the glucose transporter type 4 (GLUT4).…”
Section: Introductionmentioning
confidence: 99%